The protective effect of extra-virgin olive oil in the experimental model of multiple sclerosis in the rat. (2nd January 2020) - Conde, C.; Escribano, B.M.; Luque, E.; Aguilar-Luque, M.; Feijóo, M.; Ochoa, J.J.; LaTorre, M.; Giraldo, A.I.; Lillo, R.; Agüera, E.; Santamaría, A.; Túnez, I.
Abstract : This study has evaluated the effect of EVOO (Extra-Virgin olive oil), OA (oleic acid) and HT (hydroxytyrosol) in an induced model of MS through experimental autoimmune encephalomyelitis (EAE). Dark Agouti 2-month old rats (25 males) were divided into five groups: (i) control group, (ii) EAE group, (iii) EAE+EVOO, (iv) EAE+HT, and (v) EAE+OA. At 65 days, the animals were sacrificed and the glutathione redox system and bacterial lipopolysaccharide (LPS) and LPS-binding protein (LBP) products of the microbiota in brain, spinal cord, and blood were evaluated. Gastric administration of EVOO, OA, and HT reduced the degree of lipid and protein oxidation, and increased glutathione peroxidase, making it a diet-based mechanism for enhancing protection against oxidative damage. In addition, it reduced the levels of LPS and LBP, which appeared as being increased in the EAE correlated with the oxidative stress produced by the disease.